2020
DOI: 10.1016/j.celrep.2020.108424
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Process of Effector Programming Governs CD4+ T Cell Fate Determination Induced by Antigenic Activation in the Steady State

Abstract: Highlights d Induction of effector precursors is inherent to T cell responses in the steady state d Effector precursors are programmed for terminal differentiation upon re-stimulation d cDC2 and functions of mTORC1 in T cells increase induction of effector precursors d Greater proportion of effector precursors decreases numbers of potential pTreg cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 163 publications
(271 reference statements)
3
18
0
Order By: Relevance
“…In addition to its specific molecular functions described above, Hopx has recently emerged as a crucial marker of the specific developmental and differentiation potentials of progenitor populations in various non-hematopoietic tissues both in human and mouse systems (Mariotto et al, 2016). The most recent results now extended such capacity of Hopx also to cells of the immune cells by uncovering the key roles of Hopx in indicating specific pre-effector differentiation potentials induced early in CD4 þ T cells following their antigen-specific activation in the steady state (Opejin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its specific molecular functions described above, Hopx has recently emerged as a crucial marker of the specific developmental and differentiation potentials of progenitor populations in various non-hematopoietic tissues both in human and mouse systems (Mariotto et al, 2016). The most recent results now extended such capacity of Hopx also to cells of the immune cells by uncovering the key roles of Hopx in indicating specific pre-effector differentiation potentials induced early in CD4 þ T cells following their antigen-specific activation in the steady state (Opejin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the preferential induction of tolerance mechanisms in the steady state is not easily reconciled with a formation of specific effector T cells during immunosurveillance. However, our recently published results revealed that in addition to promoting a conversion into pTreg cells, antigen-specific activation of T cells in the steady state unlocks a much broader potential for subsequent T cell differentiation [ 13 ]. Specifically, we uncovered that in addition to the initiation of pTreg cell conversion, T cells can also become specifically “pre-committed” in the steady state to undergo Th1/Th17 effector differentiation.…”
mentioning
confidence: 99%
“…Whereas a conversion into pTreg cells requires the continuous presence of tolerogenic signals, the imprinted programs promote effector differentiation even under minimally skewing conditions. This work has further revealed a specific expression in such precursors of Homeodomain only protein (Hopx) [ 13 ]. Hopx is a highly evolutionarily conserved small protein that is also present in some differentiated CD4+ effector, memory, and regulatory T cells [ 13 15 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations